PROSES KOMUNIKASI PELAKU USAHA KULINER DALAM MEMPEROLEH SERTIFIKASI HALAL DI KOTA BANDA ACEH - Muhammad Reza; Yuhdi Fahrimal (Jurnal Penelitian Sosial Ilmu Komunikasi, 2021)
Halal tourism is an accelerated development program carried out by the government in several regions in Indonesia. Aceh has been designated as a center for the development of halal tourist destinations. The increasing number of Muslim tourist visits has an effect on the provision of food and beverage products (culinary). The increase in tourist visits is not matched by the availability of halal-certified food and drinks. One of the reasons is the interest of culinary business actors to seek information about halal certification. This study aims to identify the characteristics of culinary business actors and analyze their communication process in obtaining halal certificates. This research was conducted in Banda Aceh-Indonesia in January-February 2020, using survey methods and in-depth interviews. The population determination and sample selection were carried out by purposive sampling with 77 respondents from culinary businesses and simple random sampling. Data were analyzed using Partial Least Square (PLS) analysis. The results of the study show that the characteristics of culinary business actors are MSMEs which are dominated by young entrepreneurs. PLS analysis shows that the characteristic factor (0.080) has no effect on the communication process. On the other hand, institutional support (0.709) has a significant effect on the communication process..